Associations of pre-hospital statin treatment with in-hospital outcomes and severity of coronary artery disease in patients with first acute coronary syndrome-findings from the CCC-ACS project - Zhang, Lisha; Zhang, Yan; Chu, Chao; Deng, Fuxue; Zhou, Juan; Yuan, Zuyi (Frontiers in Cardiovascular Medicine, 2023)
Background: The current burden of dyslipidemia, the pre-hospital application of statins and the association of pre-hospital statins with the severity of coronary artery disease (CAD) and in-hospital outcomes in Chinese patients with first acute coronary syndrome (ACS) are very significant and remain unclear. Methods: A total of 41,183 patients who underwent coronary angiography and were diagnosed with ACS for the first time from a nationwide registry study (CCC-ACS) were enrolled. The severity of CAD was assessed using the CAD prognostic index (CADPI). The patients were classified into statin and non-statin groups according to their pre-hospital statin treatment status. Clinical characteristics, CADPI and in-hospital outcomes were compared, and a logistic regression analysis was performed to determine whether pre-hospital statin therapy is associated with in-hospital outcomes and CADPI. A sensitivity analysis was used to further explore the issues above. Results: The non-statin group had more in-hospital all-cause deaths (1.2% vs. 0.8%, P=0.010). However, no association exists between statin pretreatment and in-hospital major adverse cardiovascular events (MACEs) or all-cause deaths in the entire population and subgroups (all P>0.05). Surprisingly, statin pretreatment was associated with an 8.9% higher risk of severely obstructive CAD (CADPI ≥37) (OR, 1.089; 95% CI, 1.010–1.175, P=0.028), and similar results were observed in subgroups of females, those aged 50 to 75 years, and patients with hypertension. Conclusion: Statin pretreatment was not related to MACEs or all-cause death during hospital stay, but it was associated with a higher risk of increased angiographic severity in patients with first ACS.